The Weights of Mughal India - Willis, R.J., (Brill | Manohar Publishers & Distributors, 2024)
Amid the glorious and rich history of Indian culture, the artifacts that have most affected the majority of people, and their everyday lives have been largely overlooked. Weights, so significant in agriculture, markets, trade, jewellery, medicine, and industry, commonly get relegated to the scrapyard once their use has finished. Weights first became widely used in India in the sixteenth century, with the reforms and growing influence of the Mughal Era, a period which lasted for about 300 years. Many of the weights produced during this time are remarkable for their distinct geometric and organic forms, many of which rival the individuality and grace of the highly celebrated weights of Burma. However, by the mid-nineteenth century, the influence of European colonialism transported industrialism and its ordinarity to India, and the era of cast iron weights began. This book endeavours to tackle a subject, which so far has defied treatment, and indeed, the Indian museums are largely devoid of Mughal weights in their collections. Given the almost complete absence of recorded material on the subject of Indian weights as artifacts, the author has attempted to assemble a body of knowledge and pictorial records, based on surviving examples of the fascinating Mughal and related weights.